Application of Zinc-Based Metal-Organic Framework ZIF-8 on Paper: A Pilot Study on Visual Appearance and Effectiveness - Balliana, Eleonora; Marchand, Mathilde; Di Matteo, Valentina; Ballarin, Barbara; Cassani, Maria Cristina; Panzavolta, Silvia; Zendri, Elisabetta (Polymers, 2025)
Paper and cellulose-based materials are known for their sensitivity to humidity, which can create stresses among fibres and increase fragility. More importantly, humidity can lead to the formation of mould and stains, compromising both aesthetic value and long-term preservation, particularly for historical documents and books. This study explored the application of in situ prepared Zeolitic Imidazolate Framework (ZIF-8), a zinc-based MOF, on paper as a potential antimicrobial material. Hand-made and commercially printed papers were tested to assess the effective deposition and formation of the ZIF-8 network, with a focus on both visual appearance and physicochemical characteristics. X-ray fluorescence and diffraction, infrared spectroscopy, and scanning electron microscopy analysis confirmed the successful formation of the ZIF-8 network in all papers. The Zn content varied, as expected, depending on application time and paper characteristics. All treated papers exhibited minor variations in brilliance and showed slightly increased rigidity. The formation of white spots linked to Zn accumulation was observed, particularly in printed books where colourimetric and microscopic variations were more pronounced.